MODEL OF IMPROVING PERFORMANCE THROUGH HUMAN CAPITAL, ORGANIZATIONAL LEARNING AND SOCIAL CAPITAL IN THE REGIONAL SECRETARIAT OF SEMARANG REGENCY GOVERNMENT - Nola Atresianilova; Moch Zulfa (UNISSULA, 2017)
The purpose of this study is to analyze the effect of human capital on social capital, the effect of human capital on performance capital, the effect of organizational learning on social capital, the effect of organizational learning on performance, and the effect of social capital on performance. While the benefits of this research include theoretical benefit i.e. the development of human resource management theory, especially related to the assessment of problems affecting service professionalism, while the practical benefits are able to give results that can be used by leaders to design human capital, learning organization and social capital so that the organization’s goals can be achieved. The research was explanatory research, i.e. research that explains the effect of independent variables on dependent variable. The population in this research was employee in the Regional Secretariat of Semarang Regency Government involving 170 people. The sample of research was determined using purposive sampling, i.e. employees who have working period> 2 years, so that it was obtained as many as 120 employees as samples. The data were collected by using questionnaires, while data analysis was conducted by using SEM analysis. The result of analysis showed that there is influence of human capital on social capital, influence of human capital on performance capital, influence of organizational learning on social capital, influence of organizational learning on performance, and influence of social capital on performance. Equation model also has fulfilled the criterion of goodness of fit. Based on the result of the research, it can be concluded that human capital has an effect on social capital, human capital has an effect on performance, organizational learning has an effect on social capital, organizational learning has an effect on performance and social capital has an effect on performance.Keywords : Human Capital, Organizational Learning, Social Capital, Performance